2015
DOI: 10.3389/fnint.2015.00015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling circadian and sleep-homeostatic effects on short-term interval timing

Abstract: Short-term interval timing i.e., perception and action relating to durations in the seconds range, has been suggested to display time-of-day as well as wake dependent fluctuations due to circadian and sleep-homeostatic changes to the rate at which an underlying pacemaker emits pulses; pertinent human data being relatively sparse and lacking in consistency however, the phenomenon remains elusive and its mechanism poorly understood. To better characterize the putative circadian and sleep-homeostatic effects on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…More stable emotional patterns also influence time production tasks, exhibiting an effect of mood, fatigue, and irritability on time perception [23]. Interestingly, 12-sec interval timing did not change along the day nor throughout the year, evidencing different pacemaker rates through several interval durations [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More stable emotional patterns also influence time production tasks, exhibiting an effect of mood, fatigue, and irritability on time perception [23]. Interestingly, 12-sec interval timing did not change along the day nor throughout the year, evidencing different pacemaker rates through several interval durations [48].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent research have demonstrated the effects of the circadian clock on short-time estimation [1,13]. Both the circadian oscillator and the sleep homeostat [11] appear to influence the rate at which the pacemaker emits pulses, evidenced in overproductions [48] .…”
Section: Introductionmentioning
confidence: 99%
“…The control of CLOCK-ARNTL heterodimer levels exhibits time-dependent fluctuations, and thus modulate the synchronization capability of shorter intervals, such as second-to-minutes [ 65 , 66 ]. Agostino and Cheng [ 58 ] provided experimental evidence showing changes in dopaminergic levels in rat striatum as a function of the circadian cycle, with lower levels of dopamine during the day and a peak at night.…”
Section: Introductionmentioning
confidence: 99%
“…Given the influence of genetic variations related to the circadian rhythm on sleep homeostasis, it is easier to understand how endogenous rhythmicity influences the interval timing, as changes in the sleep-wake cycle influence the processing of shorter time intervals. Späti et al [ 66 ], analyzed the time perception of individuals who experienced sleep deprivation, and their findings showed that sustained wakefulness distorts the timing interval through pacemaker pulse oscillations over a 24-h period, with an exponential increase and saturation in the rate of the pacemaker with time constant of 18.2 h.…”
Section: Introductionmentioning
confidence: 99%